Injectable deferoxamine-loaded microsphere hydrogels for inhibition of ferroptosis and promotion of third-degree burn wound healing - Langjie Chai; Jianglong Huang; Min Wang; Yihui Huang; Zhuo Huang; Ruiyu Zhang; Lu He; Haijie Wang; Danyang Chen; Yifeng Lei; Liang Guo (Materials Today Bio)
In chronic third-degree burn wounds, high levels of inflammatory factors such as IL-1β lead to ferroptosis in surrounding cells, thereby delaying the healing process of the burn wounds. To promote the healing of such wounds, an injectable DFO@GM-H hydrogel was developed. This hydrogel was prepared by loading deferoxamine (DFO) into gelatin microspheres (GMs), and further crosslinking in a mild reaction. The resulting DFO@GM-H hydrogels demonstrated effective self-healing and injectability, rendering them well-suited for application in irregular burn wounds. DFO@GM-H hydrogels not only maintained a moist healing environment for the burn wound healing, but also exhibited the ability to slowly release DFO, therefore overcoming the limitation of the short half-life of DFO in vivo. With sustained release and enhanced stability of DFO from the injectable hydrogels, DFO@GM-H hydrogels demonstrated excellent biocompatibility, effectively promoted cell proliferation, migration and angiogenesis, showed antibacterial activity, and effectively inhibited cellular ferroptosis both in vitro and in vivo. Consequently, DFO@GM-H hydrogels accelerated the healing of burn wounds in rats via ferroptosis inhibition and enhanced cellular response. Therefore, DFO@GM-H hydrogel is anticipated to emerge as a novel bioactive dressing for the management of burn wounds.